PATTERN OF ANTERIOR UVEITIS IN KMN EYECARE - Kevin, Kevin; Lutfiamida, Rifna (Indonesian Vitreoretinal Society, 2023)
Introduction: Anterior uveitis is the most common form of uveitis, but there are relatively few anterior uveitis studies in Indonesia. The purpose of this study is to analyze the pattern of anterior uveitis in KMN EyeCare. Methods: This is a retrospective analytic descriptive study. The samples are new patients diagnosed with anterior uveitis in KMN EyeCare between 2019 – 2021. Data collected from medical records are age, gender, clinical manifestation, etiology, and visual outcome. Result: Two hundred fifty-three (253) patients are included in this study. The most common manifestations of anterior uveitis are keratic precipitates (34%), posterior synechiae (23.3%), hypopyon (7.9%), increased IOP (7.1%), and secondary cataract (6.3%). Visual outcome more than 0.5 in 90.1% of patients and below 0.5 in 9.9% of patients. The etiology is non-infectious autoimmune-related (46.7%) consists of HLA-B27 related, and rheumatoid arthritis; followed by infectious etiology (36%) consisting of herpetic, tuberculosis, cytomegalovirus, and idiopathic (17.3%). HLA-B27 anterior uveitis is more likely to affect males than females with a statistically significant p<0.05. Conclusion: The most common etiology of anterior uveitis is non-infectious autoimmune-related, especially HLA-B27-related anterior uveitis. The HLA-B27-related anterior uveitis is predominantly in males. Keratic precipitates, posterior synechiae, and hypopyon are common clinical manifestations of anterior uveitis. The visual outcomes are good in this study.